Landscape Luminaire Design for Part of the Conservation of Chudhadhuj Royal Residence, Sichang Island - Suriyothin, Phanchalath (Nakhara : Journal of Environmental Design and Planning, 2021)
Chudhadhuj Royal Residence is a historically significant place, located on Si Chang island where a vast landscape area covers both coastal and mountainous areas. Its context connects natural landscape and culture which can be termed a cultural landscape in a holistic. The researcher would like to describe the link between the design criteria and the concepts of the cultural heritage conservation and some identities of the place to meet the function of each area in designing luminaires. The objective of this article is to demonstrate the design process of landscape luminaires for walkway. The design of prototype luminaires consists of a lamppost, a bollard, and a bollard with perforated patterns. Visual design elements and principles with the design concepts were applied to these luminaires. The image of luminaires and the effect of light of each prototype were designed, developed, and tested on-site both day and night-time. The questionnaires displaying computer-simulated images in the actual context were used for an assessment by experts from various design and architectural conservation fields. The results show that these luminaires respond to architectural conservation and identities of the place both day and night-time. The prototype luminaires were improved according to the comments of the experts. Consequently, these luminaires were granted three design patents. Ultimately, the designed luminaires and the lighting master plan were applied to the landscape improvement project of the Chudhadhuj Royal Residence, operated by the Fine Arts Department. This project can be an example of architectural conservation for a cultural heritage site in the future.